2014
DOI: 10.15193/zntj/2014/94/041-055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selected Milk Protein Preparations on Growth and Survival of Lactobacillus Acidophilus as Well as on Rheological Properties of Fermented Milk Beverages

Abstract: WPŁYW WYBRANYCH PREPARATÓW BIAŁEK MLEKA NA WZROST I PRZEŻYWALNOŚĆ LACTOBACILUS ACIDOPHILUS ORAZ WŁAŚCIWOŚCI REOLOGICZNE MLECZNYCH NAPOJÓW FERMENTOWANYCH S t r e s z c z e n i eBiałka serwatkowe są źródłem bioaktywnych peptydów i zawierają aminokwasy niezbędne do prawidłowego funkcjonowania organizmu. Preparaty białek mleka zastosowane do produkcji mlecznych napojów fermentowanych wpływały stymulująco na wzrost szczepu Lactobacillus acidophilus LA-5. Dodatek α-latktoalbuminy do mleka pełnego wpłynął na skróceni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In general terms, the profile of mean values of the tested texture parameters exhibited by products fermented by T105 containing α -la ( Figure 1(b) ) demonstrated the same character as the profiles of the fermented products with CGMP addition (hardness is higher than springiness), while the rest variants of fermented beverages containing α -la exhibited a different shape of textural profile (the mean values of springiness are much higher than hardness). Moreover, it was noted that the fermented α -la-containing milk beverages exhibited higher values of springiness, gumminess, chewiness, and resilience, while the CGMP-containing products exhibited higher hardness values, which is in agreement with results described by Kozioł et al [ 75 ]. They noted that supplementation of skim milk by 1% addition of CGMP yielded products with a higher value of the hardness parameter in comparison to 1% addition of α -la.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In general terms, the profile of mean values of the tested texture parameters exhibited by products fermented by T105 containing α -la ( Figure 1(b) ) demonstrated the same character as the profiles of the fermented products with CGMP addition (hardness is higher than springiness), while the rest variants of fermented beverages containing α -la exhibited a different shape of textural profile (the mean values of springiness are much higher than hardness). Moreover, it was noted that the fermented α -la-containing milk beverages exhibited higher values of springiness, gumminess, chewiness, and resilience, while the CGMP-containing products exhibited higher hardness values, which is in agreement with results described by Kozioł et al [ 75 ]. They noted that supplementation of skim milk by 1% addition of CGMP yielded products with a higher value of the hardness parameter in comparison to 1% addition of α -la.…”
Section: Resultssupporting
confidence: 90%
“…It was revealed that addition of selected milk or whey protein preparations (in a proper concentration) to milk may improve the texture parameters of fermented milk beverages and stimulate the growth of probiotic microorganisms [ 34 , 71 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three weeks of refrigerated storage decreased the ability of WPC yoghurt to retain water by about 20%, while PWP yoghurt showed little difference (3%). The direction of the changes in the case of the use of WPC is also confirmed by Akalin et al [79], and Kozioł et al [80]. A study by Cais-Sokoli ńska and Walkowiak-Tomczak [40] also confirmed that the storage time of natural yoghurt significantly affects its WHC, obtaining values of over 90%.…”
Section: Water-holding Capacity and Syneresismentioning
confidence: 53%
“…These trends are supported by Sodini et al [ 8 ], who showed that the water-holding capacity is greater in milk-based beverages with added whey protein than without it. Kozioł et al [ 45 ] state that higher water-holding capacity in products containing WPC may result from increased cross-linking of curds compared to yoghurts not enriched with protein preparations. According to Gharibzahedi and Chronakis [ 46 ], the three-dimensional structure of yoghurt is stabilized by the reduction of syneresis resulting from cross-linking of microbial transglutaminase with milk proteins.…”
Section: Resultsmentioning
confidence: 99%